FREQUENCY OF DEPRESSION IN PATIENTS OF CHRONIC HEPATITIS C BEFORE STARTING TREATMENT - Fazal, Muhammad Owais; Bilal, Ahmed; Tahir, Ghulam Abbas; Yaqoob, Yasir; Ahmed, Kamran; Izzat, Ayesha (Journal of Pakistan Psychiatric Society, 2023)
Introduction: Pre-existing psychiatric illnesses, such as mood and psychotic disorders, are 3–4 times more common and frequently undetected in HCV patients. This could be brought on by a diminished desire to use or access mental and primary health care services, actual or imagined stigma against HCV patients, or denial of their psychiatric symptoms. Comorbid depression can impact the outcome because it is linked to decreased HCV therapy adherence.Objectives: To quantify the prevalence of depression among Hepatitis C patients not receiving treatment.Study Design: This was a cross-sectional study.Setting: Medical Department, Faisalabad Medical University and affiliated Allied Hospital, Faisalabad.Study duration: 30th December 2021 to 29th June 2022.Materials & Methods: A total of 310 patients having  Hepatitis C infection, with an age range of 20 years to 60 years, were included, while the patients suffering from an additional underlying chronic medical disease like CKD, COPD and diabetes, which can cause depression, were excluded. Demographic data, including age, gender, residence (rural or urban), education of patient (Primary,   middle or higher education), marital status (single, married or separated), income of patient and duration of Hepatitis C infection were recorded. The researcher interviewed the selected patients by using Beck Depression Inventory. Results: The study's age ranged from 20 to 60 years, with a mean age of 41.75 + 8.62. Most 163 patients (52.58%) were in the 20–40 age range. 166 (53.55%) of the 310 patients were men, and 144 (46.45%) were women, for a male-to-female ratio of 1.2:1. In our study, the frequency of depression in patients with Hepatitis C infection not receiving any treatment was found in 187 (60.32%) patients.Conclusion: The conclusion of the study is that the frequency of depression in patients suffering from Hepatitis C infection not receiving any treatment is very high.